Persistence and Extinction of One-Prey and Two-Predators System - Dubey, B.; Upadhyay, R. K. (Nonlinear Analysis: Modelling and Control, 2004)
In this paper, a mathematical model is proposed and analysed to study the dynamics of one-prey two-predators system with ratio-dependent predators growth rate. Criteria for local stability, instability and global stability of the nonnegative equilibria are obtained. The permanent co-existence of the three species is also discussed. Finally, computer simulations are performed to investigate the dynamics of the system.